2015
DOI: 10.1161/circgenetics.114.000900
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Analysis of Plasma B–Type Natriuretic Peptide in Blacks

Abstract: Background Numerous experimental studies suggest that B-type natriuretic peptide (BNP) is cardioprotective, yet in clinical studies, higher plasma BNP concentrations have been associated with incident cardiovascular disease and higher left ventricular mass (LVM). Genetic association studies may allow us to determine the true causal directions without confounding by compensatory mechanisms. Methods and Results We performed meta-analysis of two genome-wide association (GWA) results from a total of 2,790 Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 45 publications
(59 reference statements)
4
29
0
Order By: Relevance
“…Furthermore, in another study, the single nucleotide polymorphism rs4253311 in kallikrein B gene was associated with brain natriuretic peptide levels in African-Americans at a genome-wide significance. 143 Overall, these data strongly support the notion that plasma KKS functions with the RAS and the brain natriuretic peptide signaling pathways to regulate the cardiovascular system.…”
Section: Diabetes Mellitussupporting
confidence: 66%
“…Furthermore, in another study, the single nucleotide polymorphism rs4253311 in kallikrein B gene was associated with brain natriuretic peptide levels in African-Americans at a genome-wide significance. 143 Overall, these data strongly support the notion that plasma KKS functions with the RAS and the brain natriuretic peptide signaling pathways to regulate the cardiovascular system.…”
Section: Diabetes Mellitussupporting
confidence: 66%
“…Meirhaeghe et al 3 showed that the G allele was associated with a 1.8-fold higher level of promoter activity versus the A allele in cultured cells. At least 7 independent racially diverse human population studies have shown that the minor allele of rs198389 SNP is associated with elevated mean levels of NT-proBNP and/or BNP [3][4][5][6][7][8][9] with similar effect size observed for NT-proBNP and BNP levels. 6 The minor allele of rs198389 (G allele; higher BNP levels) has been associated with reduced ventricular dysfunction following coronary artery bypass grafting, 10 reduced hospital readmissions, and lower E/E 1 in patients after myocardial infarction (MI), 8 and a lower risk of developing type 2 diabetes mellitus.…”
mentioning
confidence: 99%
“…3,11,12 The minor allele of rs198389 was recently found to be modestly associated with reduced systolic BP (SBP) in a meta-analysis of African Americans. 7 Minor alleles of SNPs in the NPPA gene, associated with both increased atrial NP and BNP levels, unlike specific variants in the NPPB gene, have previously been associated with lower BP and incident hypertension 8,13 in primarily white individuals. Previous genetic association studies looking at cardiovascular outcomes have been small in size or with limited duration of follow-up.…”
mentioning
confidence: 99%
“…KLKB1 encodes the glycoprotein plasma kallikrein (also known “Fletcher factor” (28)), which acts as a proteolytic activator of several vasoactive and circulating peptides (kinins) (29,30). Accordingly, SNPs in KLKB1 showed genome-wide associations with vasoactive peptides (plasma bradykinin (31,32), active renin (rs3733402) (33), BNP in Blacks (34), aldosterone/renin ratio in Europeans (34), MR-pro-ADM and CT-pro-ET-1 (rs4253238 (35), r 2  =   0.81 with our tophit). Of note, F11 is a paralog of KLKB1 and codes for the coagulation factor XI.…”
Section: Discussionmentioning
confidence: 53%